Contrasting ecosystem CO2 fluxes of inland and coastal wetlands: a meta‐analysis of eddy covariance data. (9th August 2016) - Lu, Weizhi; Xiao, Jingfeng; Liu, Fang; Zhang, Yue; Liu, Chang'an; Lin, Guanghui
Abstract: Wetlands play an important role in regulating the atmospheric carbon dioxide (CO2 ) concentrations and thus affecting the climate. However, there is still lack of quantitative evaluation of such a role across different wetland types, especially at the global scale. Here, we conducted a meta‐analysis to compare ecosystem CO2 fluxes among various types of wetlands using a global database compiled from the literature. This database consists of 143 site‐years of eddy covariance data from 22 inland wetland and 21 coastal wetland sites across the globe. Coastal wetlands had higher annual gross primary productivity (GPP), ecosystem respiration ( R e ), and net ecosystem productivity (NEP) than inland wetlands. On a per unit area basis, coastal wetlands provided large CO2 sinks, while inland wetlands provided small CO2 sinks or were nearly CO2 neutral. The annual CO2 sink strength was 93.15 and 208.37 g C m −2 for inland and coastal wetlands, respectively. Annual CO2 fluxes were mainly regulated by mean annual temperature (MAT) and mean annual precipitation (MAP). For coastal and inland wetlands combined, MAT and MAP explained 71%, 54%, and 57% of the variations in GPP, R e, and NEP, respectively. The CO2 fluxes of wetlands were also related to leaf area index (LAI). The CO2 fluxes also varied with water table depth (WTD), although the effects of WTD were not statistically significant. NEP was jointly determined by GPP and R e for both inland and coastal wetlands. However, the NEP/ R e and NEP/GPP ratios exhibited little variability for inland wetlands and decreased for coastal wetlands with increasing latitude. The contrasting of CO2 fluxes between inland and coastal wetlands globally can improve our understanding of the roles of wetlands in the global C cycle. Our results also have implications for informing wetland management and climate change policymaking, for example, the efforts being made by international organizations and enterprises to restore coastal wetlands for enhancing blue carbon sinks.